2017
DOI: 10.1080/07391102.2017.1401002
|View full text |Cite
|
Sign up to set email alerts
|

Steered molecular dynamics for studying ligand unbinding of ecdysone receptor

Abstract: Ecdysone receptor (EcR) is an important target for pesticide design. Ligand binding regulates EcR transcriptional activity similar to other nuclear receptors; however, the pathways by which ligands enter and leave the EcR remain poorly understood. Here, we performed computational studies to identify unbinding pathways of an ecdysone agonist [the selective ecdysone agonist, BYI06830] from the EcR ligand binding domain (EcR LBD). BYI06830 can dissociate from EcR LBD via four different pathways with little effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…4C) is useful as alignment template for virtual screening of EcR site-specific molecules (Harada et al, 2013), as well as BYI06830, a non-steroidal EcR activator (Hu et al, 2018). The aliphatic chain of PonA binds to Tyr118, suggesting a critical ligation for EcR activation (Hu et al, 2017). Based on ligandreceptor interactions, molecular docking can be applied as a useful and costless tool for pesticide discovery.…”
Section: Resultsmentioning
confidence: 99%
“…4C) is useful as alignment template for virtual screening of EcR site-specific molecules (Harada et al, 2013), as well as BYI06830, a non-steroidal EcR activator (Hu et al, 2018). The aliphatic chain of PonA binds to Tyr118, suggesting a critical ligation for EcR activation (Hu et al, 2017). Based on ligandreceptor interactions, molecular docking can be applied as a useful and costless tool for pesticide discovery.…”
Section: Resultsmentioning
confidence: 99%
“…To estimate the binding strength of the nanobodies to RBD, we performed SMD simulations by pulling nanobodies at constant velocities along the vector pointing away from the binding interface (Figure 5). Previous studies typically used 2.5 -50 Å /ns speeds [18][19][20][21][22][23][24][25] , which overestimate the unbinding free energy. To better estimate the unbinding free energy, we performed our simulations with a velocity of 0.1 Å −1 , comparable to the velocities used in high-speed atomic force microscopy (AFM) experiments 26 15 Steering forces were applied to the Cα atoms of the nanobody residues on the binding interface, whereas Cα atoms of RBD residues at the binding interface were kept fixed.…”
Section: Unbinding Of the Nanobodies From S Protein Under Forcementioning
confidence: 99%
“…Nanobodies are single-domain antibodies that are used in disease diagnosis and as drug carriers. 1 Because of their low molecular weight (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and complexity, they can be mass-produced rapidly at a low cost in bacteria or yeast. 2,3 Recent studies identified several nanobodies, including H11-H4, H11-D4, Ty1, Nb20, Nb6, and Sb23, [4][5][6][7][8] as promising drugs for neutralizing activity against SARS-CoV-2 infection.…”
mentioning
confidence: 99%
“…The t‐butyl and A‐ring were located in a hydrophobic part of the cavity formed by residues belonging to helixes H3, H5, H6, H11 and to the loops between helixes H6–H7 and H11–H12. It is noteworthy that the hydrogen bond formed between the carbonyl group of the ligand and Asn504 was crucial not only for stabilizing ligand binding, but also for preventing ligand escape (Hu, Hu, et al, 2018; Hu, Yin, et al, 2018). To aid the development of lead compounds, more X‐ray crystallographic structures of the ligand binding domain of EcR/USP heterodimer (EcR/USP‐LBD), in complex with several potent ecdysone agonists, have been reported (Billas et al., 2003; Browning et al., 2007; Carmichael et al., 2005; Iwema et al., 2007; Ren et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Horoiwa et al performed virtual screening based on the three‐dimensional structure of the IMD‐bound HvEcR using MM/PBSA, and five novel EcR ligands (IC 50 ranged from 9.1 to 100 μ m ) were successfully identified (Horoiwa et al., 2019). We also identified a novel lead structure of an ecdysone analogue using virtual screening based on the binding mode of DBHs, and a series of novel pyrazole amides were designed and synthesized (Deng, Xie, et al, 2016; Deng, Zhang, et al, 2016; Hu, Hu, et al, 2018; Hu, Yin, et al, 2018). However, the common characteristics of steroidal and nonsteroidal ecdysone agonists have not been determined using virtual screening.…”
Section: Introductionmentioning
confidence: 99%